Culture industries in old industrialized regions: a successful strategy for innovative regional development? - Andreas Freundt (European Regional Science Association (ERSA), 2002)
The proposed paper adresses the contribution of culture and culture industries to regional development in old industrialized regions. The need for innovative regional development strategies in these regions is high, because traditional stragies have not been successful. But how to arrange and build up innovation in a milieu, which as a rule, is not innovative? It is difficult to promote innovative milieus in old industrialised regions. Bottom-up approaches to benefit from endogenous potentials are difficult to build up in regions, which are dominated by actors, who are not innovative in general. Discussions about innovative regional development strategies and systems focuss on the analysis of the socio-economic field, the organisation and perspectives of regional economies, building up regional cluster as a concentration of innovative economic activities or questions of regional governance. I suggest to add the promotion of culture industries to this appoach. Culture in an old industrialized region: a contradiction? The paper will argue that regional promotion strategies strengthening the culture industries need to focus on a long-term and regionally orientated perspective. Key recommendations for implementing process-orientated strategies should be; the integration of the culture industries as an action field in regional development concepts; the exploration of existing culture industries profiles; the development of ideas and projects; the formulation of flagship-projects (e.g. the new Guggenheim-Museum in Bilbao) to act as a catalyst; the development of a communication network to link important actors. It will be difficult, even for old industrialized regions, to focus only on the development of endogenous potentials, e.g. the culture industries, which can only be one part of a whole regional development strategy. Exogenous support, in form of financial public support by the nation state, the funds of the European Union and the regional policies, has to concentrate on and develop regional 'networking' in these regions. Culture industries can function as one part of an holistic regional approach.
Keywords: 330